2017
DOI: 10.1017/s0272263117000110
|View full text |Cite
|
Sign up to set email alerts
|

Production and Comprehension in Processability Theory

Abstract: The purpose of this study was to determine whether processability theory (PT; Pienemann, 1998, 2005) accounts for the emergence of grammatical forms and structures in comprehension. Sixty-one learners of English participated in oral interviews that elicited a variety of structures relevant to PT. Learners were divided into two groups: those who produced these structures productively in speech (high level) and those who did not (low level). These groups then read grammatical and ungrammatical sentences with PT … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 48 publications
0
3
0
1
Order By: Relevance
“…3 out of 10) in group one and two. Yamaguchi & Kawaguchi (2016) in their study of the development of relative clauses in English L2 also found that some relative clauses emerged at the earlier stages of their informant. In fact, they indicated that relative clause constructions can be acquired at the S-procedure stage (p. 91).…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…3 out of 10) in group one and two. Yamaguchi & Kawaguchi (2016) in their study of the development of relative clauses in English L2 also found that some relative clauses emerged at the earlier stages of their informant. In fact, they indicated that relative clause constructions can be acquired at the S-procedure stage (p. 91).…”
Section: Discussionmentioning
confidence: 92%
“…An acquisition criterion provides an intelligible framework in L2 research on whether an interlanguage structure has been acquired by the leaner or not. However, acquisition has been operationalised in different ways using varied methodologies (Spinner & Jung, 2018).…”
Section: Acquisition / Emergence Paradigmmentioning
confidence: 99%
“…Among the few studies dedicated to investigating receptive grammar acquisition using the PT framework are Keatinge and Kessler (2009), Spinner (2013), and Spinner and Jung (2018).…”
Section: Study Objectivesmentioning
confidence: 99%
“…Sin embargo, algunos evaluadores destacan la falta de atención al proceso en el que se formula la información textual. Según ellos, la comprensión lectora se entiende por un proceso de extraer la información desde un texto e integrar toda la información formando un significado coherente (Spinner y Jung, 2018;Khalifa y Weir, 2009;Grabe, 2009;Anderson, 2009;Dekeyser, 2007;Pressley, 2006;Breznitz, 2006;Perfetti, Landi y Oakhill, 2005;Koda, 2005;Urquhart y Weir, 1998;Gernsbacher, 1990;.…”
Section: Introductionunclassified